2020
DOI: 10.3390/f11040449
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Structural Carbohydrate Decreased for Pinus thunbergii along Coast–Inland Gradients

Abstract: Although photosynthesis (carbohydrate production) decreases under wind load, it is unclear how carbohydrate categories allocation changes. We determined the leaf morphology (specific leaf area (SLA), needle thickness), anatomy (cuticle thickness, epidermal thickness), photosynthesis (effective quantum yield of Photosystem II (Y(II)), carbohydrate (structure carbohydrate (SC) and non-structure carbohydrate (NSC)), and environmental variables in Pinus thunbergii plantations from coast to inland, with wind speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Carbohydrate biosynthesis was a major GO term in PP vs. PS, presumably due to the involvement of starch and sugar in leaf/needle development. Similar results were also found in other plants such as Vitis vinifera ( Gao et al, 2021 ), Hevea brasiliensis ( Gersony et al, 2020 ), and Pinus thunbergia ( Zhang et al, 2020 ). Additionally, regulation of morphogenesis, organization of external encapsulating structures and cell wall biosynthesis GO terms were identified, which may be related to the difference in stem morphology (apical dominance) between P. sibirica and P. pumila .…”
Section: Discussionsupporting
confidence: 85%
“…Carbohydrate biosynthesis was a major GO term in PP vs. PS, presumably due to the involvement of starch and sugar in leaf/needle development. Similar results were also found in other plants such as Vitis vinifera ( Gao et al, 2021 ), Hevea brasiliensis ( Gersony et al, 2020 ), and Pinus thunbergia ( Zhang et al, 2020 ). Additionally, regulation of morphogenesis, organization of external encapsulating structures and cell wall biosynthesis GO terms were identified, which may be related to the difference in stem morphology (apical dominance) between P. sibirica and P. pumila .…”
Section: Discussionsupporting
confidence: 85%
“…Pinus thunbergii Parl. was the most prestigious of the coniferous bonsai trees, which was a type of positive evergreen tree native to Japan and the southern coast of Korea [ 1 , 2 ] It was widely used in coastal urban greening and coastal windbreaks due to its resistance to barrenness and strong adaptability, especially to sea fog and sea winds [ 3 , 4 , 5 , 6 ]. It has been cultivated in Qingdao City, China, since 1900 and has been widely planted in coastal cities in China for almost 120 years [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that variations in the degree of sclerophylly (as indicated by leaf mass area) would increase g res because leaves that are more scleromorphic will show thicker cuticles, but other work has demonstrated that changes in wax composition may compensate for such effect (Bueno et al, 2020). Another alternative, explored to a lesser degree, is that further reductions in g res may be inhibited by changing carbohydrate allocation priorities (Zhang et al, 2020). In other words, as non-structural carbohydrate reserve pools deplete, cuticle production to prevent cuticular water losses may be limited by NSC availability.…”
Section: Introductionmentioning
confidence: 99%